2020
DOI: 10.1002/hec.4118
|View full text |Cite
|
Sign up to set email alerts
|

The effects of paid sick leave on worker absenteeism and health care utilization

Abstract: We estimate the short-term effects of paid sick leave on worker absenteeism and health care utilization in the United States using data from the 2000-2013 Medical Expenditure Panel Survey. We use both parametric and matchingbased difference-indifferences methods to account for nonrandom selection into jobs that offer paid sick leave and estimate the treatment effect separately for workers who gained and lost sick leave benefits. We find consistent evidence of increased absenteeism among female workers who gain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Workers without paid sick leave are more likely to work while sick, which can increase contagion and lead to poor health outcomes [14,15]. Lack of paid sick leave also means workers are less likely to go to the doctor for illness or routine health appointments, which can lead to workers taking more time off in the long run [16,17]. Paid sick leave policies have the potential to reduce contagion work, but only if workers are able to access and use paid leave.…”
Section: Introductionmentioning
confidence: 99%
“…Workers without paid sick leave are more likely to work while sick, which can increase contagion and lead to poor health outcomes [14,15]. Lack of paid sick leave also means workers are less likely to go to the doctor for illness or routine health appointments, which can lead to workers taking more time off in the long run [16,17]. Paid sick leave policies have the potential to reduce contagion work, but only if workers are able to access and use paid leave.…”
Section: Introductionmentioning
confidence: 99%
“…22,27,31,34,36,45,49 A recent study by Chen and colleagues found only females, but not other groups, who gained PSL reported a small (22%), but significant increase in work absences. 22 Zimmer found those with PSL worked fewer hours when faced with a priority condition with doctorrecommended treatment, but not in the case of a nonwork injury with doctor-recommended treatment or poor health. 31 The rest of the studies reporting increased absences from work among employees offered PSL also found decreases in presenteeism and were reported in that section.…”
Section: Absence From Workmentioning
confidence: 94%
“…22,31,36,49 Ten studies investigating absence from work found that PSL increased worker absence, 22,23,29,[31][32][33]36,37,49,53 one reported fewer overall absences in the workplace, 12 and seven did not establish a significant relationship between PSL and worker absence. 22,27,31,34,36,45,49 A recent study by Chen and colleagues found only females, but not other groups, who gained PSL reported a small (22%), but significant increase in work absences. 22 Zimmer found those with PSL worked fewer hours when faced with a priority condition with doctorrecommended treatment, but not in the case of a nonwork injury with doctor-recommended treatment or poor health.…”
Section: Absence From Workmentioning
confidence: 97%
See 2 more Smart Citations